MENGUBAH LIMBAH SLUDGE PABRIK PULP DAN KERTAS MENJADI PRODUK BERGUNA - Sri Wahyono (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2000)
Pulp and paper mills are one of the important industries that contribute ingovernment’s income. Unfortunatelly, they also produce the wastes, such assludge that potentially degrade the environmental quality. The common treatments of sludge are landfilling and incinerating. However, the current trend is to recycle of sludge or it is used for producing the valuable products like absorbents, fillers, compost, etc. These are more attractives than landfilling or incinerating due to economically benefit.